Management of ankle fractures in diabetic patients: case series of seven patients - Afifi, Amgad; Daghriri, Yaquob; Alkhatib, Muhammed; Farsi , Sultan; Alragea, Ahmed; Eltayeb, Haitham; Mohabbat , Asim; Sandaqji, Danah (Journal of the Foot & Ankle, 2025)
Objectives: To evaluate the effectiveness and safety of retrograde intramedullary nailing with antibiotic-impregnated cement in the management of ankle fractures in diabetic patients with peripheral neuropathy, focusing on postoperative outcomes. Methods: This study included seven diabetic patients with traumatic ankle fractures and peripheral neuropathy. Postoperative data collection was performed, focusing on evaluating fracture healing through radiographic evidence, time to achieve full weight-bearing, and any complications, including infection, wound dehiscence, or the need for additional surgical intervention. Results: Regarding postoperative complications, among seven diabetic patients with ankle fractures, only one patient developed a medial foot ulcer. Four patients achieved full weight-bearing without pain within five months, and no cases of delayed union, malunion, or nonunion were recorded. Conclusions: Orthopedic surgeons face challenges treating ankle fractures in diabetic patients due to high morbidity and mortality rates. Our case series demonstrated that the minimally invasive tibiotalocalcaneal option may reduce infection risk and require fewer operations, with only one postoperative complication and no intraoperative issues. Level of evidence: IV, Case series